Chapter «Leontius dicit»: l'utilizzo delle glosse a Omero nella Genealogia di Boccaccio - Ceccarelli, Chiara (Studi e saggi, 2021)
Among the many sources used by Boccaccio in his scholarly work Genealogia deorum gentilium, there are also the Homeric poems, made available to the author thanks to Leonzio Pilato's Latin translation. What is interesting is that besides the Latin text of Iliad and Odyssey, he makes use also of Leonzio's glosses written in the margins of his autograph manuscripts. In the wake of Agostino Pertusi's pioneering study, this paper traces a link between Leonzio's glosses on the Odyssey (Venezia, Biblioteca Nazionale Marciana, gr. IX 29) and many passages of the Genealogia where Leonzio is quoted as a source. The analysis is structured in three parts, i.e. the quotation of Boccaccio's passage, the text of the source and a detailed commentary on its use.